Remain or return? An empirical study of influencing factors on the return of Chinese international students during the COVID-19 pandemic - Zhang, Keming; Zeng, Neng; Zhang, Kesen (Frontiers in Psychology, 2022)
Background COVID-19 is now a global public health crisis with unprecedented political, economic, and social consequences affecting nations across the world. It also has a profound impact on the mobility of international students. When the COVID-19 was under control in China, and it was spreading dramatically in the United Kingdom, Chinese international students studying in the United Kingdom have been caught in a double bind over whether to return home or not. Objective This study aims to explore the factors that influenced Chinese international students’ choices of return during the COVID-19 pandemic when the COVID-19 was under control in China, while it was spreading dramatically in the United Kingdom. Methods Taking Chinese international students studying in the United Kingdom as an empirical case, this study used qualitative and quantitative research methods to explore the factors that influenced their choices of return. Based on the Rational Choice Theory and qualitative analysis of text data, this paper constructed the influencing factors model of returning to China. On this basis, we developed a questionnaire and collected data from 1,333 students in late April and early May 2020. Binary Logistic Regression with 95% CI for odds ratio (OR) was used to identify significant factors. Results The reserve of epidemic prevention supplies (OR = 0.712), transportation expenses (OR = 0.618), and quarantine expenses (OR = 0.702) negatively affected the return choice of overseas students. The supply of daily necessities (OR = 1.495), the anti-epidemic policy of the United Kingdom (OR = 1.684), and the demand for job hunting after graduation (OR = 1.661) had positive effects. Conclusion The institutional rationality had the biggest promoting effect, replaced development rationality, and became the most important factor for overseas students to return to China during the COVID-19 pandemic. Economic rationality, which has a significant negative effect, is the biggest obstacle to returning home. These conclusions have policy implications for governments’ response to the COVID-19 epidemic and improvement of the quality of services for overseas students.